Tinjauan Teoretis Negara Kesejahteraan terhadap Keterlibatan Swasta dalam Badan Usaha Milik Negara - Yuzon Sutrirubiyanto Nova; Neni Ruhaeni; Neni Sri Imaniyati; Susanto Susanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Private involvement in State-Owned Enterprises (SOEs) is a form of strategic transformation in an effort to improve efficiency, competitiveness, and better corporate governance. The problems in this study are: a) How is the implementation of private involvement in BUMN? and b) How is the impact of private involvement on People's Welfare? The research method used is normative juridical. The conclusion of this study is that the implementation of private involvement is carried out through privatization schemes with the main objective of increasing efficiency, capital, and modernizing BUMN management. The impact of private involvement in SOEs includes increased operational efficiency, more transparent and accountable governance, and increased contribution to the national economy. However, this involvement also brings challenges such as the potential for excessive commercialization, conflicts of interest, and the risk of weakening public service functions. Therefore, strong regulations and consistent supervision are needed to ensure synergy between state and private interests in the management of SOEs.